Government Capital Expenditure: Implication for Economic Growth Prospect in Nigeria - LAWAL, Saheed Oluwaseun (The International Journal of Business Review (The Jobs Review), 2024)
The purpose of this study was to clarify the impact of government capital expenditure on economic growth. It used GDP growth as a substitute for economic growth. The capital expenditure was not considered aggregated, but was decomposed (that is, the components of the capital expenditure are taken into account). Capital expenditure components include capital expenditure in businesses and services, capital expenditure in social welfare, and capital expenditure on transfer. The model used FDI as a control variable. In this study, we used an auto regressive distributed lag model. The results of the regression show that while the current value of FDI is weak, capital expenditure in economic services does not affect economic growth. However, the previous value of FDI has had a significant impact on economic growth. At the same time, capital expenditure on transfer has a negative impact on economic growth. The model of the study is not auto-correlated, and as f-statistics shows, the model is important overall.